Caries Incidence in a Healthy Young Adult Population in Relation to Diet. (April 2017) - Rosier, B.T.; van Loveren, C.; Zaura, E.; Loos, B.G.; Keijser, B.J.F.; Crielaard, W.; Lagerweij, M.D.
In the past, epidemiological studies focused on cavitated stages of caries. The arrival of the International Caries Detection and Assessment System (ICDAS) in 2004 allowed for clinical measurements of the initial stages of enamel caries. However, since the introduction, most studies applying the ICDAS still have studied the diseased population. The objective of this cross-sectional observational study was to describe early enamel caries in a large healthy young adult population and determine the relationship with diet and oral hygiene measures. The study population consisted of 268 healthy participants without frank cavitation. The examinations were done visually and radiographically using ICDAS on all tooth surfaces. In total, 8.6% of the surfaces (occlusal > approximal > smooth) had caries, of which 92.0% were confined to enamel (28.5% ICDAS score 1, 54.0% score 2, 8.6% score 3). Thirteen percent of the occlusal and 63% of the approximal caries were found with radiography. Thus, radiography is quintessential for the diagnosis of approximal enamel lesions. We found a positive correlation between enamel caries (ICDAS 1 to 3) and the consumption of mono- and disaccharides and carbohydrates ( r = 0.226 and r = 0.188, respectively, both P < 0.01), as well as a negative correlation with alcohol consumption ( r = −0.202, P < 0.01). There was also a positive correlation between enamel caries and the energy intake from mono- and disaccharides (sugar kJ, r = 0.206, P < 0.01), which was independent of body mass index. Only 11 participants consumed less than 10% of total energy as sugar kJ, which is the recommended percentage of kJ from free sugar by the World Health Organization. No clear correlation was found with oral hygiene. In conclusion, in this healthy young adult population, caries was found in 97.8% of the subjects, mostly initial enamel caries (ICDAS 1 to 2) in the occlusal surface of molars, and was related with dietary factors.